THE ROLE OF QUIZIZZ APPLICATION IN EVALUATING STUDENTS’ LEARNING OUTCOMES IN ELEMENTARY SCHOOL EDUCATION - Aini, Nur; Saputri, Pratiwi; Sastrawati, Eka; Nazurty, Nazurty; Indryani, Indryani (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
The rapid development of information and communication technology necessitates swift adaptation to changing times, especially in the field of education, which is related to learning assessment. Previously, the learning evaluation process used conventional methods such as paper, but now it has evolved with digital-based evaluation media such as Quizizz. Quizizz is designed to help teachers and students conduct learning assessments in elementary schools. This research aims to determine how Quizizz application abilities can be used as a learning evaluation media. The qualitative method is applied in this research, using data collection in the form of literature studies related to relevant journals as the research approach. Articles from journals are dissected and reviewed for data collection, and they are taken from nationally accredited journals from Google Scholar and Sinta. The analysis of related journals found that using Quizizz media can cultivate interest and learning motivation and make learning evaluations more enjoyable with the features available on Quizizz.